Pengaruh Model Pembelajaran Guided Inquiry Berbantuan Virtual Laboratory terhadap Keterampilan Berpikir Kritis Peserta Didik - Wulandari, Wulandari; Mursali, Saidil; Dewi, Ika Nurani (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of guided inquiry learning model assisted by virtual laboratory on students' critical thinking skills. The background of this study is based on the low critical thinking skills of students, as well as the limited laboratory facilities in schools. This study uses a quantitative model with a quasi-experimental design type pretest-posttest control group design. The research sample consisted of two classes X at SMA Negeri 2 Labuapi which were selected by cluster random sampling. The research instrument was a critical thinking skills test compiled based on Ennis' indicators (2011). Data analysis was carried out using the N-Gain test and ANCOVA test. The results showed that the N-Gain value of the experimental class (0.378) was higher than the control class (0.302), and the results of the ANCOVA test showed a significance value of 0.026 (<0.05) which means that there is a significant effect of the learning model on improving critical thinking skills. These findings indicate that the guided inquiry model assisted by virtual laboratory is more effective than conventional learning in developing critical thinking skills, such as the ability to analyze information, formulate arguments, and draw logical conclusions. This model is relevant to be applied in 21st century science learning, especially in schools with limited laboratory facilities.